1996
DOI: 10.1177/02841851960371p157
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Features of Lobar Agenesis of the Liver

Abstract: Our radiographic findings can provide a multidisciplinary approach in the identification of this anatomic anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…9 Makanjuola et al reported five patients with agenesis of the right lobe of the liver, all of whom had right hypochondriac pain or epigastric pain as the presenting symptom. 6 According to Radin et al, 2 of the 24 patients with this anomaly reported in the world literature, 12 (50%) had biliary tract diseases, 9 had cholecystolithasis, 2 choledocholithiasis, and 1 carcinoma of the gallbladder. The authors speculated that the abnormal hepatic morphologic characteristics and resultant displacement of the gallbladder produce compression or torsion of the cystic duct, leading to stasis of the bile in the gallbladder and thus resulting in the observed calculus formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Makanjuola et al reported five patients with agenesis of the right lobe of the liver, all of whom had right hypochondriac pain or epigastric pain as the presenting symptom. 6 According to Radin et al, 2 of the 24 patients with this anomaly reported in the world literature, 12 (50%) had biliary tract diseases, 9 had cholecystolithasis, 2 choledocholithiasis, and 1 carcinoma of the gallbladder. The authors speculated that the abnormal hepatic morphologic characteristics and resultant displacement of the gallbladder produce compression or torsion of the cystic duct, leading to stasis of the bile in the gallbladder and thus resulting in the observed calculus formation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Thus, congenital agenesis of the right lobe of the liver, as described in the present report, is an extremely rare anomaly; only a few such case reports have appeared in the literature. [1][2][3][4][6][7][8] Clinically, such patients tend to be asymptomatic of the condition itself but are symptomatic of associated conditions such as biliary tract disease, portal hypertension, and volvulus of the stomach. 9 Makanjuola et al reported five patients with agenesis of the right lobe of the liver, all of whom had right hypochondriac pain or epigastric pain as the presenting symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hammock or U-shaped deformity of the stomach may be caused by pressure from the enlarged left liver lobe (18).…”
Section: Discussionmentioning
confidence: 99%
“…Few cases have been described in the literature [1], [2], [3], [4], [5], [6]. Absence of a lobe of the liver can be due to several events, such as neoplasia, chronic damage, trauma, prior surgical resection, and agenesis [5].…”
Section: Introductionmentioning
confidence: 99%